Buckner Thruston correspondence - Thruston, Buckner, 1763-1845.
ALS (Washington) from Thruston to U.S. representative Richard M. Johnson, regarding military pension claims made for Thruston's father, Charles Mynn Thruston, who served with the British Army in the French and Indian War and with the Continental Army in the Revolution.
U.S. senator from Kentucky (1805-1809), public official, and jurist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Johnson, Richard M. -- 1781-1850 -- Correspondence; Thruston, Charles M. -- 1789-1873.; Great Britain. -- Army -- Colonial forces -- America; United States. -- Continental Army; Military pensions -- United States; United States -- History -- French and Indian War, 1754-1763.; United States -- History -- Revolution, 1775-1783.; Jurists; Public officials -- Kentucky; Senators, U.S. Congress -- Kentucky